News management around equity private placements - Hsiao-Chen Liang; Woan-Yuh Jang (The Journal of Entrepreneurial Finance (JEF), 2017)
Private placement is the sale of securities to a limited number of qualified institutions or high-wealth investors. Although private placement is favorable for firms raising capital, it is relatively easy for managers to exploit it to benefit specific investors. Using a sample of Taiwanese private placements covering 2006 to 2010, we use both quantitative and qualitative variables to examine the determinants of the valence and tenor of media coverage around private placement announcements and study whether managers strategically perform news management. The results show that issuers will engage in news management around private placement announcements to facilitate the issue process. This phenomenon is more obvious if no insiders are participating in the placements. Voluntarily released news is more forward-looking and positive. These types of news provide investors with the issuers' anticipated future prospects and are relatively easy to create. The results also suggest that private placements are useful for resolving adverse selection and moral hazard problems through media power.
Keywords: G14; G32; 650; equity private placements; news management; information asymmetry; adverse selection; moral hazard